2012
DOI: 10.1016/j.brainres.2012.03.012
|View full text |Cite
|
Sign up to set email alerts
|

RGS2 mediates the anxiolytic effect of oxytocin

Abstract: The neuropeptide oxytocin (OT) has been shown to exert multiple functions in both males and females, and to play a key role in the regulation of emotionality in the central nervous system (CNS). OT has an anxiolytic effect in the CNS of rodents and humans. However, the molecular mechanisms of this effect are unclear. Here we show that OT induced the expression of regulator of G-protein signaling 2 (RGS2), a regulatory factor for anxiety, in the central amygdala (CeA) of female mice. Bath application of OT incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Oxytocin treatment resulted in anxiolysis and was associated with increased RGS2 expression in mice (Okimoto et al . ).…”
mentioning
confidence: 97%
“…Oxytocin treatment resulted in anxiolysis and was associated with increased RGS2 expression in mice (Okimoto et al . ).…”
mentioning
confidence: 97%
“…In rodents, direct hippocampal infusion of brain-derived neurotrophic factor (BDNF) has anxiolytic and antidepressant-like effects [41]. BDNF gene expression was also found to be up-regulated in primary cultured neurons treated with OT by microarray analysis [42]. In addition, stress and corticosterone strongly influence the phosphorylation of CREB in the hippocampus.…”
Section: Molecular Mechanism Of the Antidepressant-like Effect Of Ot mentioning
confidence: 99%
“…Multiple reports have shown a role for this RGS protein in modulating anxiety, with polymorphisms in RGS2 associated with generalized anxiety disorder (Smoller et al, 2008;Koenen et al, 2009;Hohoff et al, 2015), panic disorder Otowa et al, 2011;Hohoff et al, 2015), post-traumatic stress disorder , as well as suicide (Cui et al, 2008) in humans. Studies in mice have also shown an association between RGS2 and anxiety (Oliveira-Dos-Santos et al, 2000;Yalcin et al, 2004;Lifschytz et al, 2012;Okimoto et al, 2012) with decreased RGS2 expression causing anxiety (Oliveira-Dos-Santos et al, 2000;Lifschytz et al, 2012) and depression-like (Lifschytz et al, 2012) phenotypes. To better treat these diseases associated with RGS2, it is necessary to understand how RGS2 modulates synaptic plasticity and signaling.…”
Section: Rgs2mentioning
confidence: 99%
“…Ga q at the RGS domain (Heximer et al, 1997;Ingi et al, 1998) Hippocampus (Han et al, 2006) Presynaptic in hippocampal pyramidal neurons (Han et al, 2006) Regulates short-term synaptic plasticity in the hippocampus (Han et al, 2006) Anxiety (Doupnik et al, 1997;Lifschytz et al, 2012;Okimoto et al, 2012;Hohoff et al, 2015) Ga i/o at the RGS domain (Ingi et al, 1998;Han et al, 2006) Striatum (Labouèbe et al, 2007) Postsynaptic in dopamine neurons in the VTA (Labouèbe et al, 2007) Disinhibits GABA-mediated inhibition of dopamine neurons in the VTA (Labouèbe et al, 2007) Depression (Lifschytz et al, 2012;Mandelli and Serretti, 2013) Amygdala (Okimoto et al, 2012) NA (Not available)…”
Section: Rgs2mentioning
confidence: 99%
See 1 more Smart Citation